Tuning Oxygen Vacancies by Construction of a SiO2@TiO2 Core−Shell Composite Structure for Boosting Photocatalytic CO2 Reduction Towards CH4 - Jinshuo Li; Chi Cao; Xiaoyu Zhang; Huahua Dong; Mengfei Wang; Lin Zhang; Zihao Xing; Wensheng Yang (Carbon Energy)
ABSTRACT Controlled photocatalytic conversion of CO2 into premium fuel such as methane (CH4) offers a sustainable pathway towards a carbon energy cycle. However, the photocatalytic efficiency and selectivity are still unsatisfactory due to the limited availability of active sites on the current photocatalysts. To resolve this issue, the design of oxygen vacancies (OVs) in metal–oxide semiconductors is an effective option. Herein, in situ deposition of TiO2 onto SiO2 nanospheres to construct a SiO2@TiO2 core–shell structure was performed to modulate the oxygen vacancy concentrations. Meanwhile, charge redistribution led to the formation of abundant OV‐regulated Ti–Ti (Ti–OV–Ti) dual sites. It is revealed that Ti–OV–Ti dual sites served as the key active site for capturing the photogenerated electrons during light‐driven CO2 reduction reaction (CO2RR). Such electron‐rich active sites enabled efficient CO2 adsorption and activation, thus lowering the energy barrier associated with the rate‐determining step. More importantly, the formation of a highly stable *CHO intermediate at Ti–OV–Ti dual sites energetically favored the reaction pathway towards the production of CH4 rather than CO, thereby facilitating the selective product of CH4. As a result, SiO2@TiO2‐50 with an optimized oxygen vacancy concentration of 9.0% showed a remarkable selectivity (90.32%) for CH4 production with a rate of 13.21 μmol g−1 h−1, which is 17.38‐fold higher than that of pristine TiO2. This study provides a new avenue for engineering superior photocatalysts through a rational methodology towards selective reduction of CO2.